Front Cover: Selective Hydrogenation of Furfural in a Proton Exchange Membrane Reactor Using Hybrid Pd/Pd Black on Alumina (ChemElectroChem 22/2019). Issue 22 (24th October 2019) - Carl, Sarah; Waldrop, Krysta; Pintauro, Peter; Thompson, Levi T.; Tarpeh, William A.
Abstract : The Front Cover shows the controlled variation of furfural hydrogenation product speciation based on varying cathode formulations of hybrid Pd black and Pd on alumina support. More information can be found in the Article by S. Carl et al. on page 5563 in Issue 22, 2019 (DOI: 10.1002/celc.201901314 ).